CONEXÃO EMOCIONAL ENTRE MARCAS E CLIENTES: ANÁLISE DE CONFIABILIDADE NO MERCADO COMERCIAL - DEL VECHIO, GUSTAVO HENRIQUE (2018)
This study proposes to analyze the reliability of increasingly active customers in relation to brands that feel affinity. To contextualize the theme, consumption is first discussed in contemporary societies precisely because it is from their practices that brands extract their meaning. Understanding the brand from a communicational perspective, the stu- dy investigates what elements or characteristics allow the brand to establish a stronger emotional bond with customers, possibly generating around them a community of indi- viduals who recommend and defend it. After developing its theoretical foundation, the work advances, finally, to an exploratory study, through interviews with several clients to verify how they behave in the face of a disappointment with a brand that they trust for years. Traditionally, even preferred or important brands in the life of individuals do not seem to escape the logic of mobility or liquidity of consumption in contemporary societies, whose fragility is also notable in many other human relationships, such as in love, friendship, professions and even religions.